Wireless Sensor Based Hybrid Architecture for Vehicular Ad hoc Networks - Kashif Naseer Qureshi; Abdul Hanan Abdullah; Raja Waseem Anwar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
A vehicular Ad hoc network is an emerging and widely adopted technology because of their potentiality for innovative applications in transportation sector. Recently, the technology has been faced various challenges and rely on expensive architecture. The implementation of Wireless Sensor Network (WSN) in vehicular networks reduces the required investment and improves intelligent applications performance for driving safety and traffic efficiency. In this paper, we propose a wireless sensor based hybrid architecture for navigation systems for vehicular Ad hoc networks. The architecture is suitable for mountain range roads, where vehicles cannot communication properly. The propose architecture is used to exchange and perceive roadside information and helpful in navigation decision process and for alert messages.